Influence of a Constant Perpendicular High Magnetic Field on the Electrodeposition of Calcium Phosphate Coating - Daltin, Anne-Lise; Chopart, Jean-Paul (Magnetochemistry, 2022)
Calcium phosphate coatings were formed on a Ti6Al4V substrate by electrodeposition under a high magnetic field up to 16 T. The magnetic field was parallelly applied to the vertical surface electrode. Changes in crystal morphology of calcium phosphates were investigated as a function of the magnetic field amplitude, and the results are discussed in terms of magnetic field effects. Magnetohydrodynamic convection due to the Lorentz force could considerably reduce the formation of volcano-like structures and generate more uniform deposits without changing Ca/P ratios.
Number: 6
Keywords: calcium phosphate; crystal orientation; electrodeposition; high magnetic field; hydroxyapatite; magnetoelectrodeposition; magnetohydrodynamics; octacalcium phosphate